3D printing in design: for a future creative experience in Tunisia (Revista de Ensino em Artes, Moda e Design, 2023)
Architecture is deeply influenced by new technologies, constantly being tested by innovations and trends seeking to anchor and perform environmentally. These lightning-fast technological advances are paving the way for new forms of creativity in interior design. 3D printing, also known as additive manufacturing, is opening the door to smarter, more efficient spatial design. 3D printing technology has already seen success around the world, but the lack of knowledge and awareness of the technology in the construction sector, material characterization methods, and manufacturing questions pose a real problem for architects and interior designers in Tunisia. The questions that arise are the possibility of using the technology in the design of interior spaces, the role that innovation plays today in creating our spaces, and how to think about the intersection between design and 3D printing in the design of our living spaces? The aim of this work is to identify the challenges of creative and sustainable architectural conception in Tunisia through 3D printing, using an empirical approach based on case studies and the analysis of concrete projects. Education on 3D printing will allow us to re-examine this innovative technology, which could bring solutions to the environmental and social challenges related to construction. This paradigm shift will revolutionize our way of designing physical space, architecture, and building in a country where architecture has been influenced by multiple civilizations.
Keywords: technological innovations; 3D printing; creativity; design; interior space